Prospecção de enoil-redutases alternativas em Mycobacterium tuberculosis - Hopf, Fernanda Souza Macchi (2022)
The latest data published by World Health Organization on tuberculosis in 2021 are more alarming than the previous, revealing a notable reduction in case reports and disease treatment, allied with the increase in number of deaths, related to COVID-19 advent and the control efforts. Despite having effective treatment, tuberculosis remains a major concern, once there is diversity in resistant strains and people which have latent tuberculosis acting as disease reservoirs. Resistance mechanisms are widely studied for drug development strategies. The compound triclosan has its resistance mechanism elucidated and the relation with different enoyl-reductases subtypes described. In order to understand the pathogen’s biology, we sought to prospect possible alternative enoyl-reductases to InhA in Mycobacterium tuberculosis. The chapter 1 of this thesis is presented as a manuscript published on Frontiers in Microbiology, a review about the diversity in enoyl-reductases, organisms which possess it and their role in fatty acids synthesis. The next chapter, structured as a second manuscript, reports analysis concerning the proteins encoded by three of M. tuberculosis genes (Rv3553, Rv0021 and Rv1533), which demonstrated to be highly similar structurally to Streptococcus pneumoniae FabK proteins (SpFabK), which belongs to an alternative family of enoyl-reductases than the one which M. tuberculosis InhA belongs. For each gene, the structural modifications present in the regions corresponding to the SpFabK active site are described. Moreover, it is presented, for each gene, its vulnerability utilizing the gene silencing CRISPR interference technique, their ability to infect macrophage murine cells and the minimum inhibitory concentration for triclosan and isoniazid. Only the silencing of Rv1533 gene disturbed the growth of the bacillus under the tested conditions. Still in chapter 2, it is presented the coexpression networks for Rv3553 and Rv484 and, based on public available RNA-Seq data, the analysis of differential expression of the tree genes under different culture conditions from those experimentally studied. The obtained results reveal that Rv3553, Rv0021c and Rv1533 genes present distinct expression patterns from those found for inhA gene. At the end of chapter 2, based on differential expression patterns, considerations are made about the potential of the Rv1533 gene to act as an alternative enoyl-reductase under starvation conditions. Lastly, in chapter 3, partial results are added: essentiality data for Rv1533 gene, minimum inhibitory concentration for triclosan and isoniazid and messenger RNA quantification in silencing genes strains. Finally, the final considerations and perspectives to this study are described.